2018
DOI: 10.1111/php.12871
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Photoaging In Vitro by Repetitive UVA Irradiation: Induction of Characteristic Markers of Senescence and its Prevention by PAPLAL with Potent Catalase Activity

Abstract: To understand a role of UVA radiation in photoaging of the skin, we established a model of photoaging cells using cultured human dermal fibroblasts. Repeated low-dose UVA radiation for 10 consecutive days induced senescence in fibroblasts, characterized with (1) increased level of senescence-associated β-galactosidase, (2) flattened large cell shape, (3) accumulation of reactive oxygen species, (4) yellowish coloration and (5) expression of p16. These were also observed in chronologically aged fibroblasts (dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The cell viability of fibroblasts cultured in DMEM exposed to UVA decreased significantly, but remained at the same level as non-irradiated fibroblasts cultured in DMEM when the DMEM was replaced with fresh DMEM immediately after the UVA exposure ( Figure 1b). We previously reported that H 2 O 2 generated by UVA exposure of DMEM induces the senescence of fibroblasts [19]. Therefore, we studied the effects of catalase and glutathione (GSH) on the viability of UVA-irradiated fibroblasts cultured in DMEM and confirmed the preventive effects of those antioxidants when added to the DMEM prior to exposure with UVA ( Figure 1c).…”
Section: H 2 O 2 Generated By Uva In Dmem Is Highly Cytotoxicsupporting
confidence: 61%
See 2 more Smart Citations
“…The cell viability of fibroblasts cultured in DMEM exposed to UVA decreased significantly, but remained at the same level as non-irradiated fibroblasts cultured in DMEM when the DMEM was replaced with fresh DMEM immediately after the UVA exposure ( Figure 1b). We previously reported that H 2 O 2 generated by UVA exposure of DMEM induces the senescence of fibroblasts [19]. Therefore, we studied the effects of catalase and glutathione (GSH) on the viability of UVA-irradiated fibroblasts cultured in DMEM and confirmed the preventive effects of those antioxidants when added to the DMEM prior to exposure with UVA ( Figure 1c).…”
Section: H 2 O 2 Generated By Uva In Dmem Is Highly Cytotoxicsupporting
confidence: 61%
“…We and other research groups have demonstrated that chronic repetitive UVA radiation as well as a single high dose of UVA radiation causes cellular senescence in vitro and contributes to the induction of skin photo-aging in vivo, mostly by the generation of ROS [19,29], particularly H 2 O 2 , which has a long half-life compared with O 2 − and 1 O 2 . To induce biological reactions in the skin, UVA radiation is absorbed by molecules, called endogenous and exogenous chromophores, such as flavins, porphyrins, pterins, urocanic acid, FICZ, heme-oxygenase-1, and NADPH-oxidase.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…UV induced ROS further interferes with the cell signaling pathways resulting in the breakdown of collagen and reduction in collagen synthesis, leading to wrinkles and sagging of skin [52]. Photoaging is an accelerated aging process induced by sun exposure in skin cells [53][54][55]. We observed that pterostilbene could reduce the ROS production triggered by hydrogen peroxide as well as UVA radiations in skin fibroblast cells and protect the cells against oxidative damage and photoaging.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, PAPLAL directly activates signalling of aryl hydrocarbon receptor (AHR) and NRF2, suggesting its potential application in vitiligo treatment . Yoshimoto et al recently reported that PAPLAL with catalase activity suppresses H 2 O 2 ‐induced cellular senescence . Thus, PAPLAL treatment is expected to show many beneficial effects on oxidative stress‐mediated cellular senescence and skin diseases.…”
Section: Introductionmentioning
confidence: 99%